Menstruated Education Using Whatsapp Media to Self Care Dismenore in Nursing Class Students - Riska Epina Hayu; Eva Mayasari (Science Midwifery, 2021)
Dysminorrhea is stiffness or spasms in the lower abdomen that can interfere with daily activities, It is caused by ignorance of handling dysminorrhea properly and correctly. Menstruation education is a process of learning from individuals, groups and communities from those who don't know to know about disminore.. Menstruation education can be done through electronic media such as WhatsApp, whatsapp is a communication media that is commonly used by all groups including teenagers. The purpose of this study was to determine the Effect of Menstrual Education using Whatsapp Media on Self Care Disminore in Nursing Class Students. This type of research uses quantitative with quasy experiment research design with one group design with pretest and posttest. This research was conducted in July in SMK Kesehatan Pro-Skill Indonesia. The sample in this study was 56 respondents. The instrument used was a questionnaire with a random sampling technique. The analysis used is univariate and bivariate analysis using Dependent T test. The results showed that there was an influence of Menstrual Education through Whatsapp Media on Self care Disminore in nursing class students with a p value = 0,000 <0.005. WhatsApp can be used as one of educational media concerning self-care of dysmenorrhea.